Piazza Armerina : l'area nord dell'insediamento medievale presso la Villa del Casale : indagini archeologiche 2013-2014 - Bonanno, Carmela, (Access archaeology., 2020)
Archaeological explorations in the area north of the Roman Villa of Casale in Piazza Armerina (Sicily) were carried out in 2013-2014. Investigations on the slopes of Monte Mangone and a survey carried out in the immediate surroundings of the hill in the Colla district provide valuable new evidence regarding the extension of the medieval town.